2018
DOI: 10.1186/s12968-017-0419-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of T1 mapping and late gadolinium enhancement cardiovascular magnetic resonance imaging in patients with light chain amyloidosis

Abstract: BackgroundCardiac impairment is associated with high morbidity and mortality in immunoglobulin light chain (AL) type amyloidosis, for which early identification and risk stratification is vital. For myocardial tissue characterization, late gadolinium enhancement (LGE) is a classic and most commonly performed cardiovascular magnetic resonance (CMR) parameter. T1 mapping with native T1 and extracellular volume (ECV) are recently developed quantitative parameters. We aimed to investigate the prognostic value of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 29 publications
4
64
1
2
Order By: Relevance
“…Therefore, CMR evaluation is recommended as the first-line non-invasive diagnostic tool for CAL. 19 In our cohort, endomyocardial biopsy was performed in 26.0%, and CMR was done in 32.6% of all patients, which were high percentages, enhancing the credibility of the present study.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, CMR evaluation is recommended as the first-line non-invasive diagnostic tool for CAL. 19 In our cohort, endomyocardial biopsy was performed in 26.0%, and CMR was done in 32.6% of all patients, which were high percentages, enhancing the credibility of the present study.…”
Section: Discussionsupporting
confidence: 54%
“…The correlation between MD and native T1 suggests that the pathomechanism of amyloid infiltration affects both parameters to a similar extent. While native T1 is a useful diagnostic marker for CA, recent studies have shown that it is inferior to ECV as an independent predictor of prognosis in AL-amyloidosis as well as ATTR-amyloidosis patients [30, 31]. However, the significant number of amyloidosis patients suffering from renal failure stresses the need for a gadolinium-free substitute for ECV with potential prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, extracellular volume fraction (ECV) quantification by CMR T1 mapping technique has been introduced to evaluate DMF in vivo. Previous studies demonstrated that ECV reliably reflect the degree of DMF and, more importantly, is associated with prognosis in various cardiac diseases [12][13][14]. Thus, in this study, we hypothesized that myocardium in liver cirrhosis has structural alterations such as DMF, which could be effectively addressed by CMR.…”
Section: Introductionmentioning
confidence: 89%